Pengaruh likuiditas, profitabilitas, dan solvabilitas terhadap penerimaan opini audit going concern pada perusahaan sektor pertambangan - Devito Ardiansyah Gumilar; Amelia Oktrivina (LPMP Imperium, 2026)
This study aims to examine the effect of liquidity, profitability, and solvency on the acceptance of going concern audit opinions in mining companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach was employed using secondary data collected from annual reports and financial statements. The sample consisted of 29 companies with 87 firm-year observations selected through purposive sampling. Panel data regression analysis was conducted using EViews 13, and the Common Effect Model (CEM) was selected as the most appropriate model. The findings indicate that liquidity, measured by the Current Ratio (CR), and profitability, measured by Return on Assets (ROA), have a negative and significant effect on the acceptance of going concern audit opinions. In contrast, solvency, measured by the Debt to Asset Ratio (DAR), has no significant effect. The originality of this study lies in its focus on mining companies during the 2022–2024 post-pandemic period, providing updated empirical evidence on the financial factors influencing auditors' decisions in issuing going concern audit opinions.